Pierre Bayard's Wormholes - Warren Motte (Studies in 20th & 21st Century Literature, 2011)
The recent work of Pierre Bayard is trenchant, original, and deeply engaging. From Qui a tué Roger Ackroyd? (1998) Who Killed Roger Ackroyd? (2001) onward, Bayard's books have piqued the interest of readers well beyond the limited circle of those who habitually consume French criticism and literary theory, and have served thus to expand the horizon of possibility of critical writing in significant ways. Bayard writes in a conditional, hypothetical mode, rather than a declarative one, keenly aware of how very mobile literary objects are. Bayard is not afraid to take risks, and he searches for new forms through a process of bold experimentation. He seeks moreover to enlist his reader in that quest, proposing a contract to him or her, one whose principal clauses are articulative and ludic. Fictional worlds are incomplete, he argues, and we readers must intervene in them in order to palliate that incompletion, through our interpretations. We accede to fictional worlds through wormholes, passages joining places that are thought to be unconnected. With this interventionist model, Bayard encourages us to reconsider the way that we read fiction, and also the way that we read critical writing.
Keywords: French literature; literary theory; critical writing; conditional mode; hypothetical mode; Pierre Bayard; Qui a tué Roger Ackroyd; wormhole; interventionist model; fiction